THE INFLUENCE OF ISLAMIC COUNSELING GUIDANCE TO INCREASE THE SOCIAL CARE OF THE “PUNK” COMMUNITY IN THE ALANG - ALANG LEBAR SUB-DISTRICT - Anggraini, Rose; Noviza, Neni; Putra , Bela Janare (LP2M IAI Al-Khairat Pamekasan, 2024)
This research aims to find out the social awareness of the punk community before Islamic counseling is carried out, to find out social awareness after Islamic counseling is carried out and to find out the influence of Islamic counseling to increase the social awareness of the punk community in Alang-Alang Lebar District. This research is quantitative. This research was conducted in January 2024. The sample size for this research was 12 people from the punk community in Alang-Alang Lebar sub-district. Based on the results of the tables and graphs before the Islamic counseling was carried out, it can be seen that of the 12 people who got the highest score, there was 1 person, there were 0 people with a medium score, and 11 people had the lowest score. The social awareness of the punk community after being given treatment obtained the highest score, there were 3 people, the medium score was 1 person and the lowest score was 7 people. From the table data obtained after Islamic counseling, it can be seen that the social awareness of the punk community in Alang-Alang Lebar District after being given treatment is said to have increased. Based on the results in the N-Gain Score table, the N-gain Score value is 0.89 > 0.7, so the category obtained is high, and for the N-Gain Percent it is 89.92, this value is greater than 76% effective or means use. a method or treatment is effective. The results of the research show that Islamic counseling towards social awareness of the punk community in Alang-Alang Lebar District is significantly positive or acceptable. The significant results obtained were 0.008 > 0.05, so it was concluded that the results of the data on the social awareness of the punk community were homogeneous and the null hypothesis (H0) was accepted, namely that there was an influence of Islamic counseling services in increasing the social awareness of the punk community in Alang-Alang Lebar District.